THE IMPLEMENTATION OF SCHOOL BASED CURRICULUM (KTSP) IN THE TEACHING OF ENGLISH IN KEJAR PAKET B IN PACIRAN LAMONGAN - FAYYADH, ISYTIHAR (2011)
This research is aimed at describing the implementation of school based curriculum (KTSP) in the teaching of English in kejar paket B in Paciran Lamongan and describing the difficulties faced by the teacher in the teaching English in kejar paket B. This research is a qualitative research. The writer uses descriptive method to present the data. The data of the research are natural setting, people as human instrument, and the character of descriptive research. The implementation of school based KTSP the teaching English in kejar paket B in paciran lamongan. It can be seen in applying school based curriculum (KTSP). The teacher does use the curriculum of kejar paket B. It means there are standard competence and basic competence. The standard competences consist of syllabus and lesson plan from writing. The basic competences consist of listening and speaking, writing, and reading. The procedures are observation, building knowledge of field, joint construction of text, modeling of text, and individual of text. The activities are no indicator related genre, simple function text, transactional and interpersonal speech. The activities of the students are to work in pairs. After that, they practice.